The Vulnerability Paradox: Strengthening Trust in the Classroom. (March 2023) - Romney, Alexander C.; Holland, Daniel V.
Teachers often struggle with determining how vulnerable to make themselves in the classroom. Many teachers intuitively desire to exude strength and confidence in their teaching and view vulnerability as a hindrance to that aim. However, there exists a vulnerability paradox: the more vulnerable teachers make themselves, the stronger students' trust in teachers becomes. Drawing upon research on trust, we provide important insights for teachers to consider regarding how vulnerability can generate trust and in turn improve student learning. We then introduce three pedagogical strategies that teachers can use to demonstrate vulnerability, thereby engendering greater trust in the classroom.